PERMASALAHAN PEKERJA MIGRAN INDONESIA PADA KAWASAN PERBATASAN INDONESIA-MALAYSIA DI KABUPATEN SAMBAS KALIMANTAN BARAT - Nursyamsiah Nur (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This study aims to unravel the problem of Indonesian migrant workers in the border area of Indonesia-Malaysia in Sambas district of West Kalimantan. This research uses qualitative approach by seeing, hearing and understanding the socio-cultural symptoms that exist in the community in Kabuapten Sambas in the border area of Indonesia-Malaysia. Sambas regency became the focus of research because it porposively became a place of blessing and repatriation of Indonesian migrant workers to Malaysia. The data collection technique uses literature studies and field observations on socio-cultural phenomena in Sambas District. Of the many Indonesian Migrant Workers from Sambas District who work in Malaysia, there are several problems, such as entering Malaysia through non-procedural routes, namely without the official documents as stipulated in Law No. 18 Of 2017 On The Protection Of Indonesian Migrant Workers. It has an impact on Indonesian Migrant Workers who cannot get legal protection from the Indonesian State and do not get government insurance because it is not recorded in the official data of the national agency for placement and protection of Migrant Workers (BP2TKI). To overcome the problems that occur in the Sambas District Migrant Workers, there need to be some steps that must be taken, such as providing briefings to prospective migrant Workers who will work abroad, giving severe penalties to people who provide services to placement of Indonesian Migrant Workers abroad illegally, as well as strengthening agencies related to Indonesian Migrant Workers in carrying out their duties and functions to protect Indonesian Migrant Workers working abroad.